The interpersonal communication book - DeVito, Joseph A. 1938- (Pearson Education Limited, 2016)
"The Interpersonal Communication Book approaches the subject of communication through integrative theory, research, and hands-on methods. A threefold approach identifies important communicative concepts: choices in interpersonal situations, the theories and research that support these choices, and the communication skills necessary to effectively use these theories..."